Resistance training in children - Falk, B. (Pediatric Exercise Science, 2015)
Thematischer Kommentar zu 2 Themen: A. Resistance Training and Explosive Force—Effects and Mechanism(s) Waugh CM, Korff T, Fath F, Blazevich AJ. Effects of resistance training on tendon mechanical properties and rapid force production in prepubertal children. J Appl Physiol (1985). 2014 Aug 1;117(3):257-66. B. Effects of Resistance Training on Obese Youth—Adiposity and Psychological Effects Sigal RJ, Alberga AS, Goldfield GS, et al. Effects of aerobic training, resistance training, or both on percentage body fat and cardiometabolic risk markers in obese adolescents: the healthy eating aerobic and resistance training in youth randomized clinical trial. JAMA Pediatr. 2014; 168(11):1006-1014. Schranz N, Tomkinson G, Parletta N, Petkov J, Olds T. Can resistance training change the strength, body composition and selfconcept of overweight and obese adolescent males? A randomised controlled trial. Br J Sports Med. 2014; 48(20):1482-1488.